The women of the Bible speak : the wisdom of 16 women and their lessons for today - Bream, Shannon (Fox News Books, 2021)
Examines the lives of sixteen women who are central figures in Biblical tales, arranging them into pairs and contrasting their journeys, to help readers reflect not only on the meaning of each individual's life and how they relate to each other, but also help them find wisdom and insights on how to better navigate their own faith journeys.